2008
DOI: 10.2478/v10007-008-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of spectrophotometric methods for determination of ceftazidime in pharmaceutical dosage forms

Abstract: Ceftazidime is (Z)-(7R)-7-[2-(2-aminothiazol-4-yl)-2-(1-carboxy-1-methoxyimino)acetamido]-3-(1-pyridiniomethyl)-3-cephem-4-carboxylate pentahydrate (CFZM) (1, 2). It is a third generation cephalosporin antibiotic characterized by a broad antibacterial spectrum and resistant to beta-lactamase producing organisms in addition to its antimicrobial activity against Streptococci, Staphylococci, Pneumococci, etc. Several analytical procedures are available in the literature for the analysis of ceftazidime, via high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Various UV spectrophotometric methods are reported for the analysis of Ceftazidime alone in presence of other drugs [38][39][40][41][42] .…”
Section: Spectroscopic Methodsmentioning
confidence: 99%
“…Various UV spectrophotometric methods are reported for the analysis of Ceftazidime alone in presence of other drugs [38][39][40][41][42] .…”
Section: Spectroscopic Methodsmentioning
confidence: 99%
“…Literature survey revealed that few analytical methods are available for the individual estimation of ceftazidime in bulk drug and dosage formulations by HPLC in different pharmacopeia [3][4] . Few methods were reported for individual estimation of ceftazidime by voltammetry [5][6] , electrophoresis 7 , HPLC [8][9][10][11] and some method in visible region by UV-Vis Spectrophotometer [12][13][14][15][16][17][18] . But single estimation of this drug with mixture of methanol and distilled water as solvent has not been reported in bulk and in pharmaceutical formulation.…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey revealed that several methods have been used for estimation of ceftazidime alone which includes Spectrophotometry [5][6][7][8][9] , High Performance Liquid Chromatography (HPLC) [10][11][12] and in combination with pyridine [13] Vancomycin [14] and cefepime [15] by HPLC. Sulbactam was assayed successfully by Spectrophotometry [16] , Capillary Isotachophoresis [17] , HPLC [18][19][20][21] and Gas Chromatography-Mass Spectrometry (GC-MS) [22] .…”
Section: Introductionmentioning
confidence: 99%